Screening of Potato Varieties in Relation to Yield and Processing Quality: Screening of Potato Varieties (South Asian Journal of Agriculture, 2025)
Good quality potato is the main bottleneck for the expansion and improvement of potato processing industry in Bangladesh. Application of suitable organic manure viz., vermicompost also with required fertilizers might be improved its processing quality. From the perspective, four years consecutive experiments were carried out in the research field of Sher-e-Bangla Agricultural University (SAU), Dhaka-1207 from November, 2015 to April, 2018. Thirty-six (36) potato varieties were used as treatment under  this experiment  namely: Asterix, Cardinal, Rojato, Destiny, Festa Pakri, Tel Pakri, Bot Pakri, Stick, Dora, Granolla, BARI Alu-68, Raja, Binella, Dheera, Sagita, Patrones, Courage, Provento, Felsina, Multa, Lady Rosetta, Meridian, Forza, Saikat, Laura, Ailsa, Cumbica, Omera, Rumba, Jerla, Elgar, Doly, Agila, Quincy, Almerah and Steffi. The design used in this experiment was RCBD. The results revealed that, among the thirty-six potato varieties, Lady Rosetta, Asterix, Courage, Destiny, Doly and BARI Alu-68 exhibited the best results for tuber yield, specific gravity and dry matter content.South Asian J. Agric. Vol. 11, No. 2, Dec., 2025: 71-77